Operation Victory - De Guingand, Francis Wilfred, Sir Maj. Gen., 1900-1979 (London Hodder And Stoughton, 1953)
Marshal Montgomery's Chief of Staff records his experiences from a visit to France and Germany in 1937 through World War
Include Map and Appendix
Keywords: World War (1939-1945)